Learning Methods in the Teaching and Learning Process - Nadila Nadila; Euis Latipah; Silviyawati Silviyawati (Penerbit Presisi Pustaka, 2025)
This article explores various teaching methods used in the learning process and their impact on the effectiveness and quality of education. Teaching methods are strategies applied by educators to achieve optimal learning outcomes. A range of approaches—such as cooperative learning, project-based learning, problem-based learning, lectures, group discussions, and technology-assisted instruction—are examined in terms of their strengths, weaknesses, and classroom applications. By understanding the characteristics of each method, teachers can select approaches that align with students’ needs and learning potentials. The discussion indicates that using diverse and adaptive teaching methods can significantly enhance student motivation, engagement, and learning outcomes. Therefore, a deep understanding of instructional methods is an essential competency for professional educators